Technetium-99m Radiopharmaceuticals: A Review on Basic and Applied Aspects - Khan, M.; Mehmood, Q. (The Nucleus, 2020)
Technetium-99m (99mTc) usage is increasing worldwide at a rate of 32% per annum. Enriched Uranium- 235 is irradiated at nuclear reactor and subsequent process produces Molybdenum-99 (99Mo) which decays to 99mTc, and 99mTc converts to 99gTc. Organic molecules are used as 99mTc carriers, e.g., 99mTcmercaptoactyltriglycine. 99mTc is excreted from body with feces and urine. It is estimated that 0.22%â€“ 38.41% of 99mTc remains in needles and rest is injected to the patient. Forty generators per week are supplied to medical centers in Pakistan and 1.72 x105 Bq/y 99gTc is returned as radioactive waste. Every used 99Mo/99mTc generator contains 99gTc 83.3 Bq. 99gTc radioactive waste is increasing world-wide, as its global use is 4.5Ã—1014 Bq/week. No satisfactory method exists for 99gTc immobilization although incorporation of 99gTc into Fe(III) or Sn(IV) oxide matrix before glass immobilization is suggested. The present review covers all aspect of 99mTc radiopharmaceutical life-cycle and suggests options for 99gTc radioactive waste management.